Comparison of mechanoreceptor quantities in hip joints of developmental dysplasia of the hip patients with normal hips. Issue 1 (January 2014) - Desteli, Engin Eren; Gülman, Ali Birol; Imren, Yunus; Kaymaz, Figen
Background: Joint mechanoreceptors are afferent neural elements involved in pain sensation and tactile sense. Questions/purposes: We aimed to detect the free nerve endings (FNE) and other types of mechanoreceptors and to compare their quantities in human hip joint capsule (HJC) and ligamentum capitis femoris (LCF) of babies with developmantal dysplasia of hip (DDH) and intrauterine ex foetuses (control group) to find out whether there is an increase in the amount of mechanoreceptors in hip joint due to the occured anatomical chages. Patients and methods: We took 15 LCF and HJC biopsies from 15 patients undergoing hip surgery for DDH, and 15 HJC and LCFs from intrauterine ex fetuses. Total of 60 specimens were investigated. The mean age of the babies was 10.3 months (6-18 months) at the time of surgery. Full thickness 1 × 1 cm HJC and LCF portions were taken as biopsy specimens. An immunohistochemical technique was performed for neurogenic protein S-100 and examined under light microscopy. Results: FNEs were detected in all four different tissues (type IVa). Other types of mechanoreceptors (Type I-II and III) were not detected in any of the specimens. The positive rates of FNE staining in the control group were % 2.60 ± 1.24 for the LCF and % 2.67 ± 1.11 for the HJC respectively and FNE staining in the DDH group were found to be % 2.67 ± 1.11 for the LCF and % 2.73 ± 1.16 for the HJC. We did not find a statistically significant difference in number of FNEs between the specimens of the DDH group and the control group (p>0.05), also there was no statistically significant difference in number of FNEs between the HJC and LCF within each group (p>0.05). Conclusion: Our results suggest that the number of FNEs does not increase in HJC and LCF of DDH patients even though LCF hypertrophy and capsular elongation occurs.